"So I suppose you want to ask me why I spared the werewolves" - Patricia Skorge (Wissenschaftliche Einrichtung Oberstufen-Kolleg der Universität Bielefeld, 2023)
Given the premise that the core skills for future education are creativity, communication, collaboration and critical thinking (Bialik & Fadel, 2015), the case for making (collaborative) creative prose writing a central activity in the English classroom is stronger than ever. In the quest to express and shape their own meanings, learners are propelled into "languaging" activities (Swain & Watanabe, 2013) that drive effective language learning. Scaffolding with a strong appeal to learners in the digital age can be provided by online tools of various kinds. Some are explicitly designed to support creative writers, no matter what their L1, others are tools the L2 creative writer can access online. I will present examples of these resources and argue that online tools such as text generators or writing prompts represent a specific kind of born-digital text, often serving as a draft, skeleton or stem for a new creative text. I will also argue that, with guidance from teachers and used purposefully in collaborative settings, such born-digital texts (exemplified here by a blurb produced by a text generator) can give learners experience in working with the kinds of "substantial texts" that Martín Alegre (2021) fears might be displaced by an overemphasis on digital media in the English Language classroom.